2020
DOI: 10.1515/spma-2020-0109
|View full text |Cite
|
Sign up to set email alerts
|

Distance Matrix of a Class of Completely Positive Graphs: Determinant and Inverse

Abstract: AbstractA real symmetric matrix A is said to be completely positive if it can be written as BBt for some (not necessarily square) nonnegative matrix B. A simple graph G is called a completely positive graph if every matrix realization of G that is both nonnegative and positive semidefinite is a completely positive matrix. Our aim in this manuscr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Observe that, for n = 2 with m j = 1, 1 ≀ j ≀ r, the graph is a complete bipartite graph K 2,r+1 , with the following vertex partition {u 0 , u 2 } and {u 1 , v j 1 ; 1 ≀ j ≀ r}. Thus, using [6,16], the result follows. Next to prove (ii), we assume m s = 2l + 1, where l β‰₯ 1.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Observe that, for n = 2 with m j = 1, 1 ≀ j ≀ r, the graph is a complete bipartite graph K 2,r+1 , with the following vertex partition {u 0 , u 2 } and {u 1 , v j 1 ; 1 ≀ j ≀ r}. Thus, using [6,16], the result follows. Next to prove (ii), we assume m s = 2l + 1, where l β‰₯ 1.…”
Section: Discussionmentioning
confidence: 90%
“…Proof. In literature, the graph n = 1 with m j = 1, 1 ≀ j ≀ r, is denoted by T r and in [6], it was shown that det D(T r ) = (βˆ’1) rβˆ’1 2 rβˆ’2 . To prove (ii), we assume m s = 2l, where l β‰₯ 1.…”
Section: Discussionmentioning
confidence: 99%
“…We also provide the inverse of the distance matrix for a class of multi-block graphs with cofactor zero. Consequently, as a special case to multi-block graphs, we compute the determinant and inverse of the distance matrix for a class completely positive graphs, which improves the class studied in [4]. .…”
Section: Discussionmentioning
confidence: 99%